POTENTIAL ABILITY OF THE SOLANUM-FEEDING LADYBIRD BEETLE HENOSEPILACHNA DIFFINIS (COLEOPTERA; COCCINELLIDAE) TO USE THE INTRODUCED FABACEOUS PLANT CENTROSEMA MOLLE - Kikuta, Shogo; Fujiyama, Naoyuki; Kahono, Sih; Kobayashi, Norio; Hartini, Sri; Katakura, Haruo (Treubia, 2014)
-